Possibility of Stabilizing Peat Soil Using Electroosmotic Method - Amaruddin, Haslin Idayu (Universiti Teknologi Petronas, 2008)
Major construction problems related to structure on soft soil such as peat are low shear strength and large compressibility. Peat soil normally, very high in water content and has low dry density. Thus, it has low shear strength.